Implementasi Tiketing Wisata Berbasis Flutter dan Laravel dengan Fitur Dashboard Analitik Pengunjung - Bibit Raikhan Azzaki; Pungkas Subarkah; Nandang Hermanto (Institut Teknologi Garut, 2026)
This study aims to design and implement a digital-based tourism ticketing system at the Curug Pinang tourist attraction as a replacement for the existing manual recording system that still relies on tear-off tickets and conventional bookkeeping. The manual system has the potential to cause errors in recording visitor and transaction data and makes it difficult for managers to compile periodic visitor and revenue reports, particularly monthly reports. The research method used is system development with the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and deployment. The system is developed using the Flutter framework as a mobile-based ticketing and cashier application, and Laravel as the backend integrated with a database and a web-based analytics dashboard. System testing is conducted using the Black Box Testing method to ensure that all system functions operate in accordance with the specified requirements. The results show that the developed digital ticketing system is able to replace manual recording, reduce transaction recording errors, and facilitate the automatic recapitulation of visitor and revenue data. Therefore, this system improves data management efficiency and supports operational decision-making at the Curug Pinang tourist attraction.